Perioperative cardiovascular risk and preventions of patients with post-COVID-19 condition - Sixu Lai; Su Min (Heliyon)
COVID-19 infectious is still a widely prevalent disease today. Although most patients with COVID-19 infection are mild. Some patients still develop to post-COVID-19 conditions, significantly increasing the perioperative cardiovascular risks. To better assess and prevent the perioperative cardiovascular risks of patients with COVID-19 infection, the safety and effectiveness of clinical practice can be improved through comprehensive measures, such as medical history collection, detection of symptoms and signs, application of auxiliary examinations, selection of scales and related rehabilitation treatment.